Preparation and characterization of cellulose - based polymer electrolytes for humidity sensors application / Fauziah Wan Mohd Noor - Wan Mohd Noor, Fauziah (2009)
Conventional polymer electrolytes use synthetic polymer. This work is an effort to substitute synthetic polymer by eco – friendly “ biopolymer” for developing proton conducting polymer. Methyl cellulose (MC) was used as host polymer and orthophosphoric (H3PO4) acid was the ionic dopant. A further modification was done by dispersing SiO2 fillers to obtain polymer – ceramic composites. All films were prepared by “solution – casting technique”.